Enhancing EFL Writing Instruction through Problem-Based Learning: Insights from a Classroom-Based Study - Fiddin, Muhammad Faqihna; Hafifah, Tasya Marsanda; Augustin, Regina Fitria; Librata, Harit Ananda; Priyantin, Tina; Ruswardiningsih, Dini (Jurnal Pedagogy, 2025)
The study aims to find out how the implementation of the Problem-Based Learning (PBL) model can enhance the writing skills of tenth-grade students, particularly in composing English exposition texts. This study applied a Classroom Action Research (CAR) method, conducted in two cycles following the stages of planning, acting, observing, and reflecting. The research was carried out in a public senior high school in Indonesia and involved 35 students. Data were gathered through writing tests, classroom observations, and student reflections. The findings revealed a steady improvement in students’ writing performance across five key aspects: organization, content, grammar, mechanics, and vocabulary. The percentage of students who met the minimum mastery criterion (score ≥76) increased from 25.71% in the pre-cycle to 42.86% in Cycle 1, and reached 60% in Cycle 2. The most notable improvement occurred in organization and content, while grammar and mechanics progressed more gradually. The use of real-life problems, collaborative discussions, and reflective writing helped students produce more coherent and persuasive exposition texts. This study was limited by its short duration and the small scope of participants, which may affect the generalizability of the results. Therefore, future research is recommended to implement more extended cycles, apply the PBL model to various writing genres, and explore the integration of digital tools to support writing development, especially in grammar and mechanics.